2011
DOI: 10.1002/pon.2067
|View full text |Cite
|
Sign up to set email alerts
|

Persistent impact of illness on families of adult survivors of childhood central nervous system tumors: a population‐based cohort study

Abstract: Adverse cancer-related consequences affect a considerable portion of families of childhood survivors of central nervous system tumor, even after reaching adulthood. The impact is aggravated by lasting sequelae and perceived shortcomings of long-term follow-up, factors that partly are avoidable. Improved clinical follow-up should particularly address illness information and long-term health-care needs to reduce the impact on families of survivors suffering from chronic health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…Thirty‐six quantitative papers reported on risk or protective factors, including 2 low in sibling‐specific scientific merit …”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐six quantitative papers reported on risk or protective factors, including 2 low in sibling‐specific scientific merit …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these issues may be important to understanding other phenomenon such as the caregivers’ overall psychosocial adjustment; however, they may not be as important to explaining caregivers’ perceptions of competence. In fact, another study of long-term survivors of childhood brain tumors also found that other issues overshadowed age and time since diagnosis in explaining family related phenomenon (Hovén et al, 2011). The results of this study concerning caregivers for AYA survivors of childhood brain tumors confirm previous research as well as provide new insights into the role of the survivor’s health in caregivers’ appraisals about their caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…The demands or burdens experienced by caregivers are associated with reports of their health; caregivers who experience more demands report less optimal health (Klassen et al, 2007; Klassen et al, 2011; Raina et al, 2004; Vance, Eiser, & Horne, 2004). As Raina proposed, caregivers who perceive that their survivor has less than optimal health undergo more caregiver demands (Bandura, 1991; Hovén et al, 2011), a relationship which is also tested in this research. While used as an outcome measure in Raina’s model, caregiver health is tested in terms of its association with caregiver demands because of the long term impact of caregivers’ emotional and physical health on managing the demands of that role (Deatrick et al, 2009; Hardy et al, 2008; Raina et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Parents of cancer survivors in another study reported persistent but decreasing posttraumatic stress symptoms five years after treatment . For some parents, long‐term psychosocial consequences persist long into survivorship . However, a Swedish study of bereaved parents found that 74% of parents had worked through most or all of their grief by four to nine years after their child's death .…”
Section: Introductionmentioning
confidence: 99%